Antidiabetic Potential of Green Seaweed Enteromorpha prolifera Flavonoids Regulating Insulin Signaling Pathway and Gut Microbiota in Type 2 Diabetic Mice. Issue 1 (19th December 2018) - Yan, Xin; Yang, Chengfeng; Lin, Guopeng; Chen, Yuqing; Miao, Song; Liu, Bin; Zhao, Chao
Abstract: This study aimed to investigate the antidiabetic activity of water–ethanol extract of green macroalgae Enteromorpha prolifera (EPW) and its flavonoid‐rich fraction less than 3 kDa (EPW3) in type 2 diabetic mice induced by streptozotocin and a high‐sucrose/high‐fat diet. The major active compounds were identified using ultra‐performance liquid chromatography coupled with quadrupole‐time‐of‐flight‐tandem mass spectrometry. Quantitative gene expression analysis of the insulin signaling pathway was performed. The effects of EPW3 on gut microflora in diabetic mice were analyzed by high‐throughput 16S rRNA gene sequencing. The results showed EPW3 treatment decreased the fasting blood glucose, improved oral glucose tolerance, and protected against liver and kidney injury with reduced inflammation in diabetic mice. The active principle of EPW3 revealed hypoglycemic effect as indicated by activation of the IRS1/PI3K/AKT and inhibition of the JNK1/2 insulin pathway in liver. Furthermore, the treatment significantly enriched the abundance of Lachnospiraceae and Alisties, which were positive correlation of metabolic phenotypes. These findings indicated that EPW3 possessed great therapeutic potential as adjuvant therapy for type 2 diabetes.